Standardized Construction of Judicial Determination Rules for Trademark Rights Abuse - Gao, Fei (Technium Social Sciences Journal, 2026)
In the judicial practice of China, determining whether an act constitutes an abuse of trademark rights typically hinges on assessing whether the acquisition and exercise of such rights violate the principle of good faith or exceed legitimate limits as the fundamental criteria. However, this standard is highly abstract, making it susceptible to misuse during application, which in turn can lead to significant uncertainty in judicial outcomes. Moreover,In judicial rulings, it is typically impossible to directly apply the principle of prohibiting trademark rights abuse to determine specific legal consequences based on the facts of a case. Based on this, this paper aims to begin with the fundamental definition of abuse of rights, examine the manifestations of abuse of rights in the field of trademark law and the application of the principle of prohibiting abuse of rights in trademark law, introduce the method of dynamic system theory , identify the factors and weights that need to be considered in determining whether an exercise of rights constitutes abuse of rights, and draw on the Alexy principle theory to attempt to standardize the judicial determination rules of trademark rights abuse. It outlines and demonstrates a specific analysis framework and examination path that can be applied to individual cases, with the aim of providing useful reference for applying the principle of prohibiting abuse of rights to effectively regulate improper exercise of trademark rights.